Evaluasi Model CIPP CADET Training Program di SMA Progresif Bumi Shalawat - Arisatul Ainiyah; Karwanto Karwanto; Mustaji Mustaji; Amrozi Khamidi; Muhammad Nur Salim (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to obtain a clear picture of the problems studied in this case, which is the purpose of this study, namely to determine the results of the evaluation of the Context, Input, Process and Product of the Cadet Training Program at SMA Progresif Bumi Shalawat. Evaluation research refers to "systematic investigations to determine the success of a particular program" (Barker, 2003, p. 149) This study uses a literature study method with a qualitative approach to explore the Stufflebeam model evaluation consisting of four dimensions, namely: context, input, process, and product, so that the evaluation model is named CIPP. The four words mentioned in the abbreviation CIPP are the targets of the evaluation, namely the components and processes of a program activity. Data were collected from various relevant national and international journals in the 2020-2024 period. The results of the study indicate that the CIPP Model provides a comprehensive framework for evaluating the Cadet Training Program at SMA Progresif Bumi Shalawat. By analyzing the context, input, process, and product, this evaluation can help improve the quality of the program and provide greater benefits to students. Through systematic evaluation, programs can be adjusted to the needs of students and the community, so as to achieve the expected educational goals.  Keywords: Evaluation Literature Study. Cadet, Training Program